Defect-assisted saturable absorption characteristics in Mn doped ZnO nano-rods. Issue 108 (19th October 2015) - Singh, Avanendra; Kumar, Samir; Das, Ritwick; Sahoo, Pratap K.
Abstract : After reaching a threshold doping level of Mn, it is possible to alter from two photon absorption to saturable absorption in ZnO nanorods. Abstract : We have investigated the effect that manganese (Mn)-doping in ZnO sub-wavelength rods (or nanorods) has on nonlinear optical properties, namely two-photon absorption (TPA) and nonlinear refraction using the single-beam Z-scan technique. Mn-doped ZnO nanorods (NRs) were prepared by a low temperature aqueous growth technique. The results show that the Mn-doping concentration primarily determines whether ZnO NRs will exhibit saturable absorption (SA) or two-photon-absorption (TPA) characteristics in an open-aperture experiment. At high Mn-doping concentrations, ZnO NRs exhibit SA behaviour which can be attributed to a high occupation probability of defect states as well as the saturation of linear absorption of sub-wavelength rod aggregates at high optical fluence. In contrast to high Mn-doping concentration in ZnO NRs, we observed TPA features in 0.5% Mn-doped ZnO NRs. The employability of such structures in the area of optical limiting and switching is essentially derived from the possibility to tune the nonlinear optical absorption which could be realized by appropriate Mn-doping in ZnO NR architecture.